A testament of hope: the essential writings and speeches of Martin Luther King, Jr - King, Martin Luther (HarperOne, 1991)
Speeches, writings, interviews, authobiographical reflections and excerpts from five of Martin Luther King's books are presented in chronological order within topical groupings. Subjects are nonviolence, social policy, integration, black nationalism, the ethics of love and hope, and more. There is also a comprehensive introduction which critiques Dr. King's actions and accomplishments and their results. Detailed commentaries head the topical divisions, and there is a bibliography in the appendix.